Polypyrrole/Ionic Liquid/Au Nanoparticle Counter-Electrodes for Dye-Sensitized Solar Cells: Improving Charge-Transfer Resistance at the CE/Electrolyte Interface. Issue 5 (2nd February 2019) - Loguercio, Lara Fernandes; de Matos, Carolina Ferreira; de Oliveira, Matheus Costa; Marin, Graciane; Khan, Sherdil; Dupont, Jairton; Teixeira, Sergio Ribeiro; Balzaretti, Naira M.; Santos, Jacqueline F. Leite; Santos, Marcos J. Leite
Abstract : To provide a viable alternative for counter electrodes used in dye sensitized solar cells, polypyrrole (PPy) based films have been synthesized via electrochemical deposition in the presence of the ionic liquid 1-butyl-3-methylimidazolium bis-(trifluoromethanesulfonyl) imidate (NTf2 ) and incorporated with gold nanoparticles (Aunanop ). The films were analyzed by SEM, UV-Vis-NIR, Raman, Electrochemical impedance spectroscopy, Cyclic voltammetry and Conductivity measurements. The presence of the ionic liquid is found to result in a more conductive film, to improve catalytic reduction of I3 − and the electrochemical reversibility of the electrode. In addition to increase conductivity, impedance spectroscopy has shown that incorporating Aunanop in the PPy/NTf2 film helps improving the interfacial charge transportation, the electrocatalytic properties and solar energy conversion efficiency. DSSCs assembled with PPy based CE presented nearly the same J-V characteristic parameters as observed from conventional Pt based device.